Response of Polypropylene Composites Reinforced with Natural Fibers: Impact Strength and Water-Uptake Behaviors - Vallejos, María Evangelina (2023)
Composites from polypropylene (PP) reinforced with hemp strands (HS) are prepared in the current work with the aim of deepening on the influence of this reinforcement on the impact performance of these specific composites. Despite all the research conducted in this field, the effect of this natural reinforcement on the absorbed energy during crack formation and propagation is not fully tackled in previous research works. From the methodology and samples’ geometry, the results concluded that the quality of the interface has a noticeable role in the impact resistance of these materials. The interface strength, fiber dispersion and fiber pullout are the main contributors to crack formation, whereas fiber pullout is the main one responsible for crack propagation. Maximum values of absorbed energy were found for PP composites comprising 20–30 wt% of HS and 8 wt% of the coupling agent for the un-notched samples, whereas maximum absorbed energy values corresponded to PP composites with 40 wt% of HS and 4 wt% of coupling agent for the notched samples. The water-absorption behavior in different humid environments is also examined. From the kinetic study, the water diffusion followed a Fickean behavior showing low-diffusion coefficients, increasing with fiber content. This systematic investigation represents a contribution to the analysis of the potential of reinforcing conventional polymers with natural materials, as a strategy towards more sustainable development.